Resistance of guava and araça to Meloidogyne mayaguensis - Almeida, Eduardo José de; Santos, Jaime Maia dos; Martins, Antonio Baldo Geraldo (Pesquisa Agropecuaria Brasileira, 2010)
The objective this work was to identify Myrtaceae species resistant to Meloidogyne mayaguensis. Araça and guava accessions obtained from the Collection of Native and Exotic Fruitful Plants of Unesp/FCAV, and accessions of araça plant obtained from native forest fragments located in the northeast region of the São Paulo state and the Triângulo Mineiro region, Minas Gerais state, Brazil, were tested for resistance to M. mayaguensis. The seedlings received 4,000 eggs and second stadium juveniles of M. mayaguensis each and were reared in a greenhouse. After 150 days, the genotypes were evaluated for resistance to the nematode based on the reproduction factor. Three Psidium spp. and one Eugenia accessions were resistant to M. mayaguensis.